POLICY IMPLEMENTATION OF E-PROCUREMENT PROCUREMENT USING THE E-PURCHASING METHOD IN WEST KALIMANTAN PROVINCE - Sindy Putri Dwitami (JPASDEV : Journal of Public Administration and Sociology of Development, 2023)
Sindy Putri Dwitami. Procurement of goods/services electronically (e-procurement) is one of the government's efforts to create value for money (maximum value of benefits) through the use of technology. Through Presidential Instruction Number 2 of 2022, the Regional Government is mandated to encourage the acceleration of domestic products and/or products of Micro, Small Enterprises, and Cooperatives in each region to be displayed on E-Purchasing. This study aims to analyze and provide recommendations for the Implementation of Goods and Services Procurement Policy by E-Procurement using the E-Purchasing method in West Kalimantan Province based on West Kalimantan Governor Regulation Number 58 of 2022 concerning Governance of Government Goods/Services Procurement Based on Smart E-Procurement in the Environmental Government of the Province of West Kalimantan. The theory used in this study is the theory of policy implementation according to Charles O'Jones, namely the organization of interpretation and application. The data analysis method used in this qualitative research is descriptive analysis. The results of the study show that the implementation of goods/services procurement policies by e-procurement using the e-purchasing method in West Kalimantan Province has not run optimally. This can be seen from the fact that there are still regional apparatuses who use manual shopping for goods and services, lack of storefronts, many business actors are not used by regional apparatuses, are late in placing orders for goods, server disturbances occur, there are various regulations that are not in line and confuse regional apparatuses. , and Bank Kalbar Virtual Account payments have not been integrated with Mbz. Researchers provide suggestions, namely to form a regional catalog team, make policies and improve socialization and coordination with regional apparatus regarding the implementation of e-procurement of goods and services procurement using the e-purchasing method. delays in ordering goods, server disruptions occur, there are various regulations that are inconsistent and confusing for regional apparatus, and Bank Kalbar Virtual Account payments have not been integrated with Mbz. Researchers provide suggestions, namely to form a regional catalog team, make policies and improve socialization and coordination with regional apparatus regarding the implementation of e-procurement of goods and services procurement using the e-purchasing method. delays in ordering goods, server disruptions occur, there are various regulations that are inconsistent and confusing for regional apparatus, and Bank Kalbar Virtual Account payments have not been integrated with Mbz. Researchers provide suggestions, namely to form a regional catalog team, make policies and improve socialization and coordination with regional apparatus regarding the implementation of e-procurement of goods and services procurement using the e-purchasing method.